Towards a metamaterial approach for fast timing in PET: experimental proof-of-concept. (19th September 2019) - Turtos, R M; Gundacker, S; Auffray, E; Lecoq, P
Abstract: Achieving fast timing in positron emission tomography (PET) at the level of few tens of picoseconds of picoseconds is limited by the photon emission rate of existent materials with standard scintillation mechanisms. This has led to consider quantum confined excitonic sub-1 ns emission in semiconductors as a viable solution to enhance the amount of fast-emitted photons produced per gamma event. However the introduction of nanocrystals and nanostructures into the domain of radiation detectors is a challenging problem. In order to move forward along this line, the standard bulk detector geometry and readout should be updated to allow for the implementation of new materials and within others, compensate for some of their intrinsic limitations. In this paper we will cover two study cases in which a fast emitter is combined with state-of-the-art scintillators in a sampling geometry designed to provide better timing for a fraction of the 511 keV events. For this test, we use a fast plastic scintillator BC-422 able to deliver a detector time resolution (DTR) of 25 ps FWHM (equivalent coincidence time resolution CTR of 35 ps) and we combined it with LYSO or BGO 200 m thick plates building a sampling pixel composed by two active scintillating materials. We develop a new proof of concept readout that allows for the identification of different types of events, carrying standard or improved timing information. Results are showing a DTR of 67 ps FWHM (equivalent to a CTR of 95 ps) for one third of the events depositing 511 keV in the BGO  +  BC-422 mm 3 sampling pixel. The other two third of the 511 keV events perform like standard bulk 3 mm long BGO crystals with a time resolution of around 117 ps (equivalent to a CTR of 165 ps). For the case of LYSO  +  BC-422 sampling pixel, shared 511 keV events reach a DTR of 39 ps (CTR of 55 ps) in comparison to 57 ps (CTR of 83 ps) for 511 keV events fully contained in LYSO of the same size. This work is a step forward in the integration of fast semiconductor nanocrystals and nanostructures with present detector technologies.